(untitled) (American Journal of Pedagogical and Educational Research, 2025)
Higher-order thinking skills, including critical, analytical, and creative thinking, play a pivotal role in modern English language education. These skills enable learners not only to comprehend and use the language effectively but also to analyze information, solve problems, and generate innovative ideas. This paper examines the significance of integrating higher-order thinking skills into English language teaching, emphasizing instructional strategies that promote active engagement, reflective learning, and cognitive growth. The study highlights how incorporating tasks that stimulate reasoning, creativity, and problem-solving can enhance both linguistic proficiency and intellectual development. Findings suggest that fostering higher-order thinking within English classrooms is essential for preparing learners for the complex cognitive demands of the 21st century.